Resistance to compression and microstructure of concrete manufactured with supersulfated cements-based materials of volcanic origin exposed to a sulphate environment - Cabrera Luna, Karina; Escalante García, José Ivan; Nieves Mendoza, Demetrio; Maldonado Bandala, Erick Edgar (Revista ALCONPAT, 2018)
This research presents the results of concretes made with supersulfated cements (SSC) volcanic material bases. The concretes were cured under two regimes one for 24 h at 25 ° C and one for 22 h at 60 ° C and then at 25 ° C. The specimens were exposed to two conditions, dry under laboratory conditions and immersed in a solution with 3.5% CaSO 4 at 25 ° C for up to 180 days. After 180 days, the concrete with a 5% An-10% PC-10% CaO-75% PM cementant exposed to the CaSO4 solution achieved a compressive strength of 46 MPa and 44 MPa dry under conditions of laboratory. The microstructure was analyzed by scanning electron microscopy, energy dispersive spectroscopy and XRD, showing that the main hydration products are C-S-H and ettringite.